2015
DOI: 10.1515/jppr-2015-0016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bio-agents on pathogenic fungi associated with roots of some deciduous fruit transplants and growth parameters in New Valley Governorate, Egypt

Abstract: Root rot and wilt disease complex was detected in several fig (Ficus carica L.), grapevine (Vitis vinifera L.), and pomegranate (Punica granatum L.) transplants in nurseries and new orchards of the El-Kharga, Baris, Balate, El-Dakhla, and El-Farafrah districts, of the New Valley governorate, Egypt. The percentage of root rot/wilt incidence and severity on fig, grapevine, and pomegranate transplants in the surveyed districts differed. The average percentages of root rot/wilt incidence and severity, in the surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…It is native to Iran and Turkey but has been cultivated throughout the Mediterranean region and northern India since ancient times123. Pomegranate fruit is rich in a variety of compounds such as alkaloids, flavonoids, anthocyanins, steroids, sterols, vitamin C, fatty acids, organic acids, tannins, and several resinous and polyphenolic substances.…”
mentioning
confidence: 99%
“…It is native to Iran and Turkey but has been cultivated throughout the Mediterranean region and northern India since ancient times123. Pomegranate fruit is rich in a variety of compounds such as alkaloids, flavonoids, anthocyanins, steroids, sterols, vitamin C, fatty acids, organic acids, tannins, and several resinous and polyphenolic substances.…”
mentioning
confidence: 99%
“…Soil-borne pathogenic fungi viz. F. oxysporum, F. Equisetai F. solani F. semitectium and F. moniliforme caused root rots of date palm trees in both locations of New Valley governorate under study, El-Kharga and El-Dalkla Oasis (El-Morsi et al, 2009, Arafat et al, 2012and El-Morsy et al, 2015. Pathogeni city tests showed that Fusariu moxysporum, F. solani and F. Moniliforme were the causal agents of root rot and wilt diseases on date palm seedling.…”
Section: Discussionmentioning
confidence: 93%
“…A considerable role in limiting the populations of these pathogenic fungi inhabiting the above ground parts of plants is played by antagonistic microorganisms. Such properties are first of all exposed by the arbus cular mycorrhizal fungi (AMF) and/or Baker ' s yeast (BY) (El-Mehalawy, 2004, El-Morsi, et al, 2009and Ziedan et al, 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Disease severity was estimated using the disease rating scale (El-Morsi et al, 2009). Isolation and purification of associated fungi: Samples were thoroughly washed with tap and distilled water for surface sterilization.…”
Section: Survey and Disease Documentationmentioning
confidence: 99%